The Influence of Transformational Leadership and Principals' Motivation on the Performance of SDN 31 Bathin Solapan Teachers - Nurhamidah, Nurhamidah; Masrul, Masrul; Wahyuni, Molli (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of transformational leadership and principal motivation on teacher performance at SDN 31 Bathin Solapan. The problem in this study is based on field findings that teacher performance is still not optimal, which is indicated by the lack of innovation in learning, low discipline in compiling teaching materials, and minimal teacher involvement in professional development activities. This study uses a quantitative approach. Data collection techniques use questionnaires and observations. The sample in this study amounted to 15 teachers, with multiple linear regression analysis techniques. The results of the study indicate that: (1) transformational leadership has a significant effect on teacher performance, with a significance value of 0.001 0.05 and tcount ttable (8.077 2.703); (2) principal motivation also has a significant effect on teacher performance with a significance value of 0.001 0.05 and tcount ttable (8.841 2.703); (3) Simultaneously, transformational leadership and principal motivation have a significant effect on teacher performance with a significance value of 0.000 0.05 and Fcount Ftable (7.405 3.89). Thus, it can be concluded that the higher the quality of transformational leadership and principal motivation, the better the teacher performance at SDN 31 Bathin Solapan